The Qur'an on art, architecture & built environment - Spahic, Omer (IIUM Press, IIUM; UNISSA Press, UNISSA, 2022)
The Holy Qur’an and the Sunnah of Prophet Muhammad (pbuh) signify a conceptual foundation of Islamic art, architecture and the whole universe of the built environment. They furnish the Muslim built environment professionals, policy makers and users alike with an inspired outlook on life and those issues that are pertinent to the realm of the built environment. They also provide some broad rules of morality and guidelines of proper conduct which may or may not be directly related to art, architecture and built environment. Those principles and teachings account for the core of the Islamic monotheistic (tawhid or God’s Oneness) worldview and ethical system. Muslims are thus invited to establish such built environment theories, systems and styles which will be consistent with their religious preferences and the exigencies of their diverse epochs, geographical regions, cultures, socioeconomic conditions and other practical needs and requirements. Indeed, the whole Islamic built environment is a symbiosis between permanence or perpetuity, which is represented by the constant inclinations of the primordial human nature and the heavenly revelation and guidance, and impermanence or transience, which is necessitated and controlled by the vicissitudes of life. The sophisticated world of the Islamic built environment declined and struggled to retain its conspicuous identity principally when its two defining poles were bartered. This happened when the sacred in the Islamic built environment was compromised and regarded as a transient and man-generated legacy; when either the building system or the style of an age or a geographical zone became excessively venerated and regarded as a sole inspiration and guidance; or when a complete detachment from the direction of the Islamic message and its civilization occurred and an inspiration and guidance were sought from foreign sources instead, which entailed incompatible worldviews and ethical systems. It follows that the success in reviving the authentic meaning and vigour of the Islamic built environment depends entirely on properly conceptualizing its basic notions and theoretical frameworks, which then should be followed by finding and actualizing appropriate strategies and methods for it. This book aims to contribute towards the prospect of reviving the Islamic built environment as a theory and practical reality. It discusses a number of salient built environment aspects and features exclusively based on the Qur’anic worldview as the fountainhead of all wisdom and guidance. The topics deliberated are those revolving around the concepts of architecture, art, sustainable development, peaceful coexistence with the natural environment, decoration (aesthetics), housing and mosques. A cluster of relevant Qur’anic surahs (chapters), and sets of relevant Qur’anic verses (ayat), have been identified and interpreted for the purpose. The attained results are expected to enrich the domains of the Islamic built environment theories and its codes of professional conduct significantly. They could also enhance, as well as Islamise, the Islamic built environment educational programmes and curricula, impacting in turn on the quality and appropriateness of the occupational output of the Muslim built environment professionals. The book is divided into six chapters, each chapter dealing with either a single theme or more based on a selected Qur’anic surah, or a set of Qur’anic verses. Those chapters are: 1. The Mosque of Mischief versus the Mosque of Piety (the relationship between the Islamic worldview and architecture); 2. Lessons in Decoration from Surah al-Zukhruf (Gold Adornments); 3. Lessons in Art and Architecture from Surah al-Shu’ara’ (the Poets); 4. Lessons in Architecture and Sustainable Development from Surah al-Nahl (the Bee); 5. Lessons in Peaceful Coexistence with the Environment from Surah al-Naml (the Ants); 6. Lessons in Housing from Surah al-Nur (the Light).